DEVELOPMENT OF CONTEXTUAL EDUCATION TO IMPROVE GRADUATE COMPETENCE OF BIOLOGY EDUCATION STUDY PROGRAM - Entin Daningsih; Yokhebed Yokhebed; Endi Nursapikka; Widya Qamariah; Apriani Apriani; Aulia Rahma Chaniago; Gita Faramita (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura)
The students must prepare their best education and have good characters to compete due to tight globalization. This study aimed to describe the process of character building with contextualism. The method used in this research was quantitative descriptive with contextualism approach which has seven stages in its implementation namely contructivism, questioning, investigation, learning community, modelling, reflection, and authentic assesment. There were five students as a reseach team involving in this study. Students went through the first three stages by finding superior fruits and made their products and related to syllabus curriculum 2013. They chose laboratory work to implement their products in schools. The reflection stage was shown by the capability of the team to do the authentic assesment in the schools. They fullfilled questionnaire containing nine indicators of characters as an authentic assessment. All character scores were high except innovation score indicating improving innovation require more experience and learning process.